Mitochondrial genome rearrangements at low taxonomic levels: three distinct mitogenome gene orders in the genus Pseudoniphargus (Crustacea: Amphipoda). (2nd September 2016) - Stokkan, Morten; Jurado-Rivera, Jose A.; Juan, Carlos; Jaume, Damià; Pons, Joan
Abstract: A comparison of mitochondrial genomes of three species of the amphipod Pseudoniphargus revealed the occurrence of a surprisingly high level of gene rearrangement involving protein-coding genes that is a rare phenomenon at low taxonomic levels. The three Pseudoniphargus mitogenomes also display a unique gene arrangement with respect to either the presumed Pancrustacean order or those known for other amphipods. Relative long non-coding sequences appear adjacent to the putative breakage points involved in gene rearrangements of protein coding genes. Other details of the newly obtained mitochondrial genomes – e.g., gene content, nucleotide composition and codon usage – are similar to those found in the mitogenomes of other amphipod species studied. They all contain the typical mitochondrial genome set consisting of 13 protein-coding genes, 22 tRNAs, and two rRNAS, as well as a large control region. The secondary structures and characteristics of tRNA and ribosomal mitochondrial genes of these three species are also discussed.